Religious And Traditional Practices For Turkish Women With Gynecologic Cancer - Duman, Mesude; Yüksekol, Özlem Doğan; Ozan, Yeter Durgun (My University, 2018)
Aim: The aim of this study is to analyze the religious and traditional practices performed by Turkish women with gynecologic cancer in orderto heal.Material And Methods: This descriptive study was conducted with thepatients with gynecologic cancer receiving treatment in the GynecologyClinic, Ambulatory Chemotherapy Unit and Oncology services of a university hospital located in Eastern Turkey between 1 January-31 December 2017. The study was completed with 116 patients.Results: In this study, it was revealed that 59.5% of the participants began to pray/perform salaat, 20.7% drank holy water, 19.8% began to usecharms, 15.5% visited tombs, 12.1% used herbal therapies, 9.5% visitedreligious clergymen, 6.9% had lead poured, 6% made a vow/ sacrifice;6% had amulets prepared for themselves, and 5.2% had treatment magicfor themselves.Conclusion: Consequently, many patients with gynecologic cancer preferto perform religious and traditional practices as an additional treatmentto the modern cancer treatment. Furthermore, it was revealed that theirinformation source were unreliable sources such as their circle and media in general.
Keywords: Tamamlayıcı ve Entegre Tıp; Onkoloji